The influence of brand image, service quality, and customer satisfaction on repurchase intention - Harmawati, Elsa Surtina; Dewanti, Ratna Listiana (Journal of Management and Business Insight, 2023)
Purpose-This study aims to analyze the effect of brand image, service quality, and customer satisfaction on repurchase intention of consumers at McDonald's Sultan Agung Yogyakarta. Design/Methodology/Approach-This study used a quantitative approach using a questionnaire as a data collection technique, and a sample of 151 McDonald's Sultan Agung consumers was obtained. The sampling technique used is the purposive sampique, with the instrument measuring scale using a Likert scale. Hypothesis testing was carried out using multiple linear regression analysis using the SPSS version 25 analysis tool. Findings-The results of this study indicate that brand image has proven to affect repurchase intention positively. Service quality is proven to positively affect repurchase intention. The customer satisfaction is proven to positively influence repurchase intention. Research limitations/implications-Research findings are expected to be a reference and learning for producers of goods or services that to grow or retain consumers to be interested in making repeat purchases, there are many factors that influence it. This research reveals that brand image, service quality, and customer satisfaction influence consumers to be interested in making repeat purchases. Originality/value-Studies on consumer behavior in the food and beverage business are quite limited, and there are minimal studies that use fast food restaurants as research subjects to measure the level of consumer repurchase interest. The study reveals factors that are thought to influence the level of consumer repurchase interest in a fast food restaurant.